Trade Policy of Transition Economics - Jose Luis Moraga; Jean-Marie Viaene (Tinbergen Institute, 2000)
This paper focuses on ignored issues regarding the impact of trade reforms in transition economies. These economies are primarily characterized by a low quality of their products, large depreciations of their currencies, and a high degree of government intervention in economic activity. These elements are embedded in a duopoly model of vertical product differentiation and international trade. First, we show that trade liberalization in transition economies reduces the output of local firms. Second, neither free trade nor zero subsidy is optimal. There exists a rationale for infant-industry protection in that a commitment by the government to use a socially optimal trade and industrial policy can release the domestic firm from low-quality production. Since greater profits are derived from high-quality products, this enables local firms to finance productivity and technology improvements. Third, in terms of social welfare, no equivalence result between the effects of exchange rate changes and the optimal trade policy can be obtained.
Keywords: F12; F13; P31; 330; Exchange Rates; Hedonic Prices; Leapfrogging; Optimal Trade Policy; Product Quality; Trade Liberalization; Systemtransformation; Übergangswirtschaft; Außenwirtschaftspolitik; Wechselkurs; Hedonischer Preisindex; Produktqualität; Theorie